2020
DOI: 10.9734/ijbcrr/2020/v29i830215
|View full text |Cite
|
Sign up to set email alerts
|

Oral Acute & Sub-Chronic Toxicity Assessment of Ethanol Leaf Extract of Simarouba glauca

Abstract: Traditional herbal medicine and their preparations have been widely used for thousands of years and are still in use in developing and developed countries owing to their medicinal values and their presumed relative safety. This belief that medicinal plants are not toxic or are with less side effect due to their natural origin is debatable; hence this study was conducted to evaluate the safety and (or) toxicity of Ethanol leaf extract of Simarouba glauca (EESG) on liver, kidney and heart functions of Wistar rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Although, it is not unlikely that the observed increase in plasma triglycerides and LDL-cholesterol may have resulted from chylomicrons formed from dietary lipids due to the inability of the liver to effectively metabolize the lipids and synthesize bile salts. A previous article earlier published from our laboratory revealed that oral administration of EESG at similar doses resulted in congestion and hepatic inflammation (Osagie-Eweka et al, 2020); this may well be responsible for the poor dietary cholesterol metabolism by the liver, hence elevations in plasma lipids. Furthermore, it is most likely that increase in glucose breakdown; coupled with increased pentose phosphate pathway activity can increase acetyl-CoA yield (precursor) for fatty acid synthesis.…”
Section: Effect Of Oral Administration Of Eesg On Oxidative Stress Bi...mentioning
confidence: 81%
“…Although, it is not unlikely that the observed increase in plasma triglycerides and LDL-cholesterol may have resulted from chylomicrons formed from dietary lipids due to the inability of the liver to effectively metabolize the lipids and synthesize bile salts. A previous article earlier published from our laboratory revealed that oral administration of EESG at similar doses resulted in congestion and hepatic inflammation (Osagie-Eweka et al, 2020); this may well be responsible for the poor dietary cholesterol metabolism by the liver, hence elevations in plasma lipids. Furthermore, it is most likely that increase in glucose breakdown; coupled with increased pentose phosphate pathway activity can increase acetyl-CoA yield (precursor) for fatty acid synthesis.…”
Section: Effect Of Oral Administration Of Eesg On Oxidative Stress Bi...mentioning
confidence: 81%
“…As a result, according to the OECD's Globally Harmonized System of Classification [28], the ethanolic S. pinnata seed extract can be classified as category 5 with a relatively low acute toxicity hazard. In this study, food and water consumption and body weight changes were also measured to monitor the toxicity of the S. pinnata extract since these parameters can also be used to indicate the harmful effects of extracts [49]. Food and water consumption were not significantly different between the untreated control and negative control groups.…”
Section: Discussionmentioning
confidence: 99%
“…To substantiate the potentiality and reported in 1961. the first quassinoide structure was elucidated . More than 200 currently known chemicals are isolated and identified from Simaroubaceae family (Balu et al, 2020;Osagie-Eweka et al, 2021). Most of these secondary metabolites showed potential biological activities in bioassay systems posing structures which could be considered as effective therapeutic and bioactive agents (Vikas et al, 2017).…”
Section: The Apoptotic Properties Of Leaf Extracts Of Simarouba Glaucmentioning
confidence: 99%